Study of spectrum of fungal isolates in the sputum of newly diagnosed pulmonary tuberculosis patients. (January 2022) - Wani, Abdul Raouf; Kumar, Lokender; Singhal, Ritu; Chakraborti, Amartya; Khot, Sagar Mohanrao
Tuberculosis is a state of immunosupression which exposes the patients to further opportunistic pathogens like fungus. Methods: 102 newly diagnosed sputum positive pulmonary tuberculosis cases were enrolled. Significant fungal isolates were seen in 31/102 (30.4%) patients. Aspergillus spp. were isolated in 13/31(41.9%) of the positive fungal cultures while Candida spp. were isolated in 15/31 (48.4%). Low body mass index, duration of symptoms, haemoptysis, severity of radiological features and IgG Aspergillus antibodies were independent risk factors for positive fungal culture. Significant proportion of patients with PTB have fungal colonisation of their airways which can lead to poor clinical outcomes. Few easily ascertained clinical parameters can help the clinician to determine patients who are at a higher risk of fungal colonisation.